Enhancement of Ebola preparedness across Africa - Morozoff, C; Pigott, D; Sankoh, O; Laney, S; Hay, S (Centers for Disease Control and Prevention, 2016)
Ebola virus disease (EVD) has demonstrated the devastating impact that zoonotic diseases can have on human populations (1,2). The recent EVD outbreak exposed national and international weaknesses in existing systems of outbreak response (3). The ability for this relatively rare virus to quickly spread merits the need for better preparedness plans in at-risk countries. Because zoonotic diseases account for most emerging infectious diseases (4), effective interventions must focus on animal reservoir hosts in addition to human health-seeking behavior and health system effectiveness.